TEACHER’S WRITTEN FEEDBACK IN WRITING FOR GRADE 10 STUDENTS OF SENIOR HIGH SCHOOL - Mouna Fitriana; Anni Holila Pulungan; Juli Rachmadani Hasibuan (Universitas Negeri Medan, 2018)
This study were aimed to find out the types of teachers’ written feedback in writing which given by the teachers for grade 10, to find out the reason why teacher used those types of written feedbacks on students’ writing and also to find out the students’ response to the teacher’s written feedbacks on students’ writing of grade 10 students in SMA YAPIM Taruna Sei Rotan. This research used descriptive qualitative method and the data were collected through documentation and interview. The data collected were analyzed qualitatively. The findings found that there were two types of feedbacks namely, direct written feedback and indirect written feedback. There were 59 direct feedbacks (52%) out of 114 total feedbacks. Meanwhile, indirect feedback with 55 un-coded direct feedbacks (48%) and in this case, teacher did not use coded indirect feedback because the teacher did not understand about the codes. The reason why teacher used those kinds of written feedback on students’ writing was because it could make the students have more vocabularies. In conclusion, teacher’s written feedbacks were important to made students aware of making mistake on their writing and the students knew about their mistake easily and their writing will be better because they learn from the mistakes. In this case, most of the students felt happy when their teacher gave a correction on their writing. The students said that direct feedback was more effective than indirect feedback because they felt confuse about what the correct word is. By using the direct feedback, the students can have more vocabularies on their next writing. The findings suggested that English teachers was expected to provide a clear description of feedback on writing, especially how students perceive and interpret the feedback given.Key words: Feedback, Teacher’s Written Feedback, Students’ Writing